Cover Feature: Adsorptive Separation of Acetylene from Ethylene in Isostructural Gallate‐Based Metal–Organic Frameworks (Chem. Eur. J. 68/2019). Issue 68 (31st October 2019) - Wang, Jiawei; Li, Liangying; Guo, Lidong; Zhao, Yingcai; Xie, Danyan; Zhang, Zhiguo; Yang, Qiwei; Yang, Yiwen; Bao, Zongbi; Ren, Qilong
Abstract : An isostructural family of M‐gallate (M=Mg, Co, Ni) MOFs not only afforded excellent separation performances for the removal of C2 H2 from C2 H4, but also a remarkably high C2 H4 productivity of 85.6 mol L −1 from an 1/99 C2 H2 /C2 H4 mixture. Metal‐ion substitution, with different lengths of the metal–oxygen bonds, significantly enhanced the interaction between the C2 H2 molecules and frameworks as a result of precisely controlling the pore aperture size from 3.69 to 3.47 Å. More information can be found in the Full Paper by Z. Bao, Q. Ren, et al. on page 15516 .